Effects of Overtourism on Recidents Perceptions in Ubud District (Gianyar) - Desak Putu Candra Dewi; Yayu Indrawati; I Made Adikampana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims at examining recidents perceptions of overtourism in Ubud. The theory used to answer the problems is Carrying capacity and Doxey Irritation Index. The method used is quantitative method. In a study that is the subject of research amounted to 100, which is the surrounding community as in respondents. To determine the informant researchers used probability sampling technique, which probability sampling technique, which the researcher provides an equal opportunity for each respondent of the population to become a member of the sample. Instrument testing uses validity tests and reliability. Meanwhile, the data analysis method uses statistical analysis with multiple linear regression equation. The findings in this research is Ubud is currently in the apaty stage according to Doxey's Irridex theory. Even though the impact of tourism activities is starting to give rise to negative perceptions felt by local communities, due to economic dependence, people in Ubud feel the importance of tourism to support their daily lives. The importance of effective destination management by local authorities, along with positive tourist conduct, were underscored as two contextual elements that mitigate the adverse impacts of overtourism on residents' sentiments. These factors serve as crucial management strategies toward fostering a more sustainable destination.